(untitled) (Global Journal of Management and Business Research, 2015)
The paper analyze the logistics enterprise#x2019;s financial date using factor analysis, and analysis to questionnaire investigation of financial data for analysis using the hierarchical#xFF0C;finally build the logistics enterprise performance evaluation index system#xFF0C;determined the different